A case of disseminated angiosarcoma-like Kaposi sarcoma presenting with unusual vesiculobullous lesions - Jasmine Gill; Oluwatosin Odeshi; Muhammad N Mahmood; Parbeer Grewal (SAGE Open Medical Case Reports, 2024)
Angiosarcoma-like Kaposi sarcoma represents a recently delineated rare histomorphologic variant of Kaposi sarcoma that can be difficult to distinguish from other vasoproliferative lesions. Conventional lesions of Kaposi sarcoma encompass patches, plaques, and nodules; however, rarely vesiculobullous lesions have been described. Angiosarcoma-like Kaposi sarcoma has never been previously reported to present with vesiculobullous lesions. Herein, we describe a unique case of disseminated angiosarcoma-like Kaposi sarcoma with vesiculobullous lesions as the initial manifestation of human immunodeficiency virus infection.